Pemenuhan Kewajiban Adat sebagai Pidana Tambahan dalam RUU KUHP - Lidya Suryani Widayati (Fakultas Hukum Universitas Islam Indonesia, 2013)
“The fulfillment of local traditional obligation or obligation prevailing in the local community” as an additional crime in the Draft Plan of Criminal Code means that the law allows the regulation existing in the community (indigenous criminal law) which does not have an equivalent in the prevailing regulations of law to be a legal source”. In this matter, the law enforcers must be able to assess whether there is really a traditional crime reported by the victim. The difference between the criminal code and the indigenous criminal law principles must also be known and anticipated by the law enforcers. This research studies the additional criminal sanction from the perspective of restorative justice that is the indigenous law concept which requires the willingness and participation of the victim, perpetrator, and the community in order to find solution for the crime conducted. This research which uses the secondary data by literature study and the primary data using interview concludes that “the fulfillment of the local traditional obligation or obligation prevailing in the local community” meets the restorative justice principles. However, a comprehensive study is needed to include the restorative justice system into Draft Plan of Criminal Code and Draft Plan of Civil Code to create the synchronization and harmony between material criminal law and normative criminal law.